The complete mitochondrial genome of Hyporhamphus quoyi (Beloniformes; Hemiramphidae) - Kehua Zhu; Zhenming Lü; Bingjian Liu; Li Gong; Lihua Jiang; Liqin Liu (Mitochondrial DNA. Part B. Resources, 2018)
The complete mitogenome of Hyporhamphus quoyi was sequenced, which is a closed double-stranded circular molecule of 16,511 bp, and we analyzed the main features in terms of the genome organization, gene arrangement and codon usage. The overall base composition includes A(27.4%), T(26.0%), C(30.4%) and G(16.2%). Moreover, the 13 protein-coding genes (PCGs) encode 3804 amino acids in total, 12 of which use the initiation codon ATG except COI uses GTG, most of them have a complete stop codon, whereas Cytb ends with the incomplete stop codon represented as a single T. The phylogenetic tree based on the neighbor-Joining method was conducted to provide relationship within Beloniformes, based on 12 PCGs encoded by the heavy strand, the NJ tree demonstrated that H. quoyi has a closest relationship with Hyporhamphus intermedius, which could be a useful basis for propagation of this species.